Assessment of physicochemical, rheological, and thermal properties of Indian rice cultivars: Implications on the extrusion characteristics. Issue 6 (11th April 2022) - Bhati, Dolly; Singh, Baljit; Singh, Arashdeep; Sharma, Savita; Pandiselvam, Ravi
Abstract: The implications of physicochemical, rheological, and thermal properties of seven eminent Indian rice cultivars (PR 114, 121, 122, 123, 124, 126, and 127) on the extrusion behavior and physico‐functionalities of the extrudates were investigated. The amylose and amylopectin content of the cultivars ranged between 12.72 to 28.86% and 71.14 to 87.28% in addition with protein and crude fat content that varied from 7.05 to 9.15% and 0.49 to 1.17%, respectively. The onset ( r  = 0.98), peak ( r  = 0.95), and conclusion ( r  = 0.98) temperatures of the cultivars were in positive correlation with amylose. Likewise, pasting temperature ( r  = 0.979), final viscosity ( r  = 0.91), set back viscosity ( r  = 0.89), and stability ratio ( r  = 0.90) of the cultivars demonstrated a significant positive correlation with the amylose content. However, peak ( r  = − 0.879) and hold viscosity ( r  = − 0.89) were negatively correlated. The cultivars were extruded at feed moisture of 15%, screw speed of 500 rpm and barrel temperature of 150°C. The extrudates characteristics viz., expansion ratio—1.82 (PR 123); bulk density—184 g/cc (PR 123); specific mechanical energy—262.35 Wh/kg; water absorption index (WAI)—6.26 (PR 122); water solubility index—48.52% (PR 123); hardness—148.63 N (PR 122); and hydration power—284% (PR 122) were viably hyphenated with the physicochemical and rheological behavior of cultivars. The physico‐functional characterization of the extrudates in terms of their starch and protein structural indexes, α‐amylase susceptibility; water soluble carbohydrates and proteins revealed the possibility of exploring these cultivars as a functionally viable and diverse ingredient for the production of ready‐to‐eat extrudates. Abstract : The physico‐functional characterization of the extrudates in terms of their starch and protein structural indexes, α‐amylase susceptibility; water soluble carbohydrates and proteins revealed the possibility of exploring these cultivars as a functionally viable and diverse ingredient for production of ready‐to‐eat extrudates.